Analysis of the seismicity related to the tidal stress prior to the Mw7.8 Kahramanmaras, Türkiye earthquake - Yane Li; Lijuan Chen (Geomatics, Natural Hazards & Risk)
Based on the preliminary reference Earth model, we calculated the temporal variation of tidal shear and normal stresses on the focal fault plane of the Mw7.8 Kahramanmaras, Türkiye earthquake. For earthquakes (M ≥ 4.0) occurring along and around the East Anatolian fault zone (EAFZ) and the Dead Sea fault zone (DSFZ) between January 2002 and December 2022, we analysed tidal stress-related seismicity from two viewpoints: occurrence time and seismic strain. Seismicity was found to be significantly correlated with semi-diurnal tidal shear stress (TSS) prior to the Kahramanmaras Mw7.8 main shock. An area with significant correlation was ∼140 km northeast of the epicentre. For three and more years prior to the Kahramanmaras event, the temporal rate of seismic strain increased during periods of increasing TSS and did not change much during periods of decreasing TSS. From the above results, the increase in TSS may have facilitated the occurrence of earthquakes in the years preceding the Kahramanmaras earthquake. The reason for these tide-triggered earthquakes may be that the seismic region is loaded to a critical state. This observation may shed light on the seismogenic processes that led to the Kahramanmaras earthquake and its precursors.